Characterization of Type 2 Diabetic Patients Admitted to the Diabetes Care Center of Cienfuegos - Gisela Zerquera Trujillo; Belkis Vicente Sánchez; Elodia Rivas Alpizar; Miriam Costa Cruz (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
Foundation: to know the clinical characteristicas of people who suffer from diabetis mellitus is indispensable to undertake comprehensive and effective actions in its control and treatment. Objective: to know the clinical characteristics and the frequency of chronic complations in people with type 2 diabetis mellitus admitted to Diabetic Education and Care Center in Cienfuegos in the year 2013. Method: a descriptive study was carried out in which 396 patients were included, admitted to the center from January to December 2013. The variable analyzed were age, sex, body mass index, presence of obesity and altered waist circumference. It was explored the treatment on admission and discharge, parameters of fasting blood glucose glycemia, total cholesterol, uric acid, micro albuminuria, so as the presence of some of the most frequent chronic complications. Results: femile sex predominated, average age was 54,42 years and toxics habits which prevailed were smoking and alcohol comsumption. Half of the patients has a body mass index higher or similar to 30.0 Kg and 77.8 % had obesity at the momentof being diagnosed as diabetic. The 78.3 % has altered waist circumference. Degree 1 of the risk of developing a diabetic foot predominated. Diabetic retinopathy and diabetic nephropathy were the most frequent followed by ischemic cardiopathy. Conclusion: diabetis mellitus is appearing at ages every time earlier a dat the moment of the diagnosis there are established already macro and microvascular complications.